2017
DOI: 10.1148/rg.2017160052
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic Osteoarthropathy: Clinical and Imaging Features

Abstract: Hypertrophic osteoarthropathy (HOA) is a medical condition characterized by abnormal proliferation of skin and periosteal tissues involving the extremities and characterized by three clinical features: digital clubbing (also termed Hippocratic fingers), periostosis of tubular bones, and synovial effusions. HOA can be a primary entity, known as pachydermoperiostosis, or can be secondary to extraskeletal conditions, with different prognoses and management implications for each. There is a high association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 68 publications
2
106
0
8
Order By: Relevance
“…Nevertheless, the patient’s age, his digital clubbing, and the lack of a good clinical response to steroid therapy led us to perform additional exams and finally to the diagnosis of HOA. Hypertrophic osteoartropathy, also known as Pierre Marie-Banberger syndrome, is a condition characterized by the triad of digital clubbing, periosteal reaction of long bones and painful tenderness of the limbs, especially in the lower extremities, sometimes with synovial non-inflammatory effusions of large joints [ 3 ]. When all three clinical features are simultaneously present, a complete form of HOA is diagnosed, but most often HOA presents as an incomplete form, with the possibility of digital clubbing being absent [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the patient’s age, his digital clubbing, and the lack of a good clinical response to steroid therapy led us to perform additional exams and finally to the diagnosis of HOA. Hypertrophic osteoartropathy, also known as Pierre Marie-Banberger syndrome, is a condition characterized by the triad of digital clubbing, periosteal reaction of long bones and painful tenderness of the limbs, especially in the lower extremities, sometimes with synovial non-inflammatory effusions of large joints [ 3 ]. When all three clinical features are simultaneously present, a complete form of HOA is diagnosed, but most often HOA presents as an incomplete form, with the possibility of digital clubbing being absent [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the high association between HOA and lung malignancies [ 3 ], the patient underwent a bronchoscopy with bronchoalveolar lavage (BAL) and transbronchial biopsies of the right lung infiltrate. Unfortunately, biopsies could not be performed because of the complexity in localizing the infiltrate under fluoroscopy.…”
Section: Case Presentationmentioning
confidence: 99%
“…However, some researchers reported that abnormal production of hypoxia-induced agents, including platelet-derived growth factor (PDGF), prostaglandin E2 (PGE2), and vascular endothelial growth factor (VEGF) in patients with HPOA, was observed. 5 Therefore, subsequently, patients with primary familial hypertrophic osteoarthropathy and neonates with congenital heart disease were prescribed long-term PGE2 injections owing to the possibility of a biochemical pathway. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…1 In HOA, the pattern of periostitis is bilaterally symmetrical, a pattern also demonstrated in venous stasis, pachydermoperiostosis and thyroid acropachy. Unilateral or localised periosteal reactions may occur secondary to trauma, neoplasm and infective and inflammatory conditions (eg, osteomyelitis, arthritis).…”
mentioning
confidence: 99%